Apexification with Calcium Hydroxide vs. Revascularization - H. Boufdil; M. Mtalsi; S. El Arabi; B. Bousfiha (Case Reports in Dentistry)
Treatment of necrotic immature teeth has always been a real challenge for the clinician due to the open apex and weak root structure, which does not allow a conventional endodontic treatment. Several therapeutic options are possible to treat those teeth. Calcium hydroxide apexification is the oldest and most studied therapeutic option, but it has some disadvantages, including the long term of treatment, the possibility of reinfection, and the weakness of the wall. To solve these problems, several authors recommend the revascularization technique. This therapy allows the continuation of root edification with apical closure and thickening of the walls. The aim of our work is to compare the two therapeutic procedures, apexification with calcium hydroxide and revascularization, through a clinical case treated and followed up for 24 months at the pediatric dentistry department in Casablanca, Morocco.